(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Occupational burnout is a chronic stress syndrome in the workplace that is not successfully controlled, has many consequences and has not received adequate attention. Objective: Describe the situation burnout of the nurses in clinical departments at Thu Duc city Hospital in 2023 and learn about some related factors. Methods: Cross-sectional study, the research were nurses from clinical departments who had worked at Thu Duc city Hospital for 12 months or more. The study used Maslach Burnout Inventory scale with 22 questions with 3 components: emotional exhaustion, derpersonalization and personality accomplishment. Results: The study surveyed 180 nurses. The occupational burnout rate of nurses in clinical departments is 33.3%, of which the internal medicine department has a rate of 42.6%, the surgery department has a rate of 30.5% and the intensive care units has a rate of 24.3%. Factors related to professional burnout in nurses are: working hours more than 40 hours/week, being on duty 16 hours, frequency of night duty being 2 times/week or more, dissatisfaction with support from colleagues, unsafe working environment, intention to quit work occasionally and frequently (p < 0.05). Conclusion: Ensure that nurse working hours do not exceed 40 hours/week, limit night duty more than 2 times a week, upgrade facilities, and ensure security and order.